The artistic and scientific connections between music and mathematics - Conceição, Maria (2020)
In this article, we address the scientific and artistic connections between music and mathematics, considering the areas of knowledge with specific and universal languages. In order to identify threads that intertwine and produce interdisciplinary points, the strategies used in the research are of qualitative character searching in the literature conceptual links, and later systematization of the relation. The focus of the study was the interweaving between the musical field and the mathematical field in the connections with Set Theory, Abstract Algebra, Fractal Geometry, Number Theory, Golden Proportion and Fibonacci Number.